2017
DOI: 10.1002/sd.1712
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fair Trade on Smallholders' Capacity to Adapt to Climate Change

Abstract: The aim of this paper is to assess to what extent producers' participation in fair trade can increase their adaptive capacity and make them more resilient to climate change. Based on the adaptation deficit framework of Fankhauser and McDermott (2014) and an expert interview with 39 producer organizations from Latin America, Asia and Africa, we first determine the perception and the impacts of climate change on fair trade producers' organizations. We then analyze how fair trade is helping producers to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
(67 reference statements)
2
16
0
Order By: Relevance
“…Additionally, FOs facilitate the marketing of farm produce through their bargaining role, enabling farmers to access lucrative markets. This has a direct impact on farmers' revenues, which can be reinvested in adaptation measures [71]. Jung (2017) [72] showed that local organizations enhance actors' capacity to recover from catastrophic events through providing access to critical resources, information, and joint response planning.…”
Section: Farmer Organizationsmentioning
confidence: 99%
“…Additionally, FOs facilitate the marketing of farm produce through their bargaining role, enabling farmers to access lucrative markets. This has a direct impact on farmers' revenues, which can be reinvested in adaptation measures [71]. Jung (2017) [72] showed that local organizations enhance actors' capacity to recover from catastrophic events through providing access to critical resources, information, and joint response planning.…”
Section: Farmer Organizationsmentioning
confidence: 99%
“…We use more recent data and also provide more structure to the analysis by first clustering the certificates according to their non-compliance patterns, while the previous studies simply compute compliance scores. Our paper relates further to the empirical literature on the impact of certification in general (e.g., Van Rijsbergen et al, 2016;Cramer et al, 2017;Dragusanu and Nunn, 2018;Glasbergen, 2018;Krumbiegel et al, 2018;Borsky and Spata, 2018;Sellare et al, 2020;Dietz et al, 2020). We also contribute to the growing literature on machine learning techniques used in social sciences (e.g., Mullainathan and Spiess, 2017;Chalfin et al, 2016;Kleinberg et al, 2018) and in particular, we…”
Section: Literaturementioning
confidence: 60%
“…Engage local smallholder through education and training scheme to help them producing good quality FFB. Increase of knowledge exchange and improve social capacity is said to help with smallholders' adaptive capacity to climate change (Borsky & Spata, 2017)…”
Section: Interpretation Of Results and Recommendationsmentioning
confidence: 99%